Peningkatan kompetensi siswa SMK melalui pelatihan desain grafis dan animasi - Mahpuz Mahpuz; Muhammad Wasil; Aris Sudianto; Muhamad Sadali; Baiq Andriska Candra Permana; Hamzan Ahmadi; Suhartini Suhartini; Indra Gunawan; Imam Fathurrahman; Lalu Kerta Wijaya; Harianto Harianto; Moh. Farid Wajdi (Universitas Hamzanwadi, 2023)
Multimedia is a crucial field of study in the present era, as all professional domains require its application to aid individuals in effectively completing their tasks. However, the Multimedia field is contributing significantly to unemployment rates today. This issue partly arises from the fact that graduates in Multimedia lack the required proficiency, skills, and knowledge sought by various companies and institutions. SMK NW Kembang Kerang is a private vocational school located in East Lombok, which offers a multimedia program attracting a substantial number of students each year. Despite graduating students in this field annually, many face the challenge of inadequate competencies upon completion of their education. The lack of practical exposure during their school years hinders the alumni's ability to compete in the job market. Although numerous photo and video editing services are available in the Kembang Kerang region, it is observed that few SMK graduates are employed in this area. The school's teachers and principal comprehend this issue, attributing it to the limited opportunities for practical training experienced by the students. Consequently, to address this concern, the author conducted a competence training activity for students at SMK NW Kembang Kerang, with a specific focus on multimedia and graphic design. The objective of this training program is to enhance the students' multimedia and graphic design skills, empowering them with competent capabilities that will prove beneficial both for their personal growth and the broader community. Through this initiative, it is anticipated that upon completing their vocational education, students will possess the necessary competencies to thrive in the professional realm and contribute positively to society at large.